Quo Vadis? LIS Postgraduate Education in the Philippines / Fernan R. Dizon, Karryl Kim Sagun and Ana Grace P. Alfiler - R. Dizon, Fernan; Sagun, Karryl Kim; P. Alfiler, Ana Grace (2011)
The paper intends to shed light on the predicament faced by many Filipino librarians: the lack of local institutions offering Library and Information Science (LIS) post graduate degrees. The study also aims to look at Filipino librarians who have either completed and are currently pursuing LIS and non-LIS postgraduate education, either locally or abroad. The paper aims to illustrate the state of Philippine LIS postgraduate education by considering the number of librarians who pursued and are still pursuing postgraduate degrees, and identifying the universities they selected, locally and overseas. The data was gathered from responses to an online questionnaire posted on websites of local libraries as well as professional networks, and supported by phone interviews. Responses were further validated through electronic correspondences. The study yielded constructive information on the state of Library and Information Science postgraduate education. Most respondents pursued or are pursuing Education related postgraduate degrees within the country. Of the number of respondents, only a few pursued or are pursuing postgraduate education in Library and information Science in other countries like the United States of America, Canada, Japan and United Kingdom.